Alternatives to Detention Theory of Change Report - Dempsey, Paige M. (2016)
Our community has come a long way over the last year in strategically partnering to reform the Juvenile Justice system in Douglas County. The strengthened relationships across the system are now enabling us to ask more assertive questions and gather catalytic evidence towards change. We are also in a position to foster mutual accountability for that change. It’s up to all of us! In that light, the OYS/JDAI Data Committee has commissioned an evaluation of the Alternatives to Detention (ATD) in Douglas County and will partner with Dr. Ryan Spohn in the implementation of that process. This evaluation is meant to ground, support, and increase efficiency for our local efforts…not duplicate or impede. We are starting this evaluation by convening local stakeholders in a Theory of Change (TOC) process